Pembuktian dan Alat Bukti dalam Perkara Hukum Acara Perdata di Pengadilan Guna Menegakan Kepastian Hukum - Adiva Nurfauzi, Wahyu; Abdul Rosyid, Muhammad; Saulidia, Uswatul; Sapitri, Nopi (UNIVERSITAS SERAMBI MEKKAH, 2024)
Evidence functions as a means to strengthen the arguments of the parties to the dispute, providing an objective basis for the judge in making decisions. In this research, normative juridical research is used in the form of legal research in the form of literature which is carried out using methods by examining library materials or secondary materials. then the approach used in this research is the statutory regulations approach which carries out an analysis using statutory regulations which are related to the issues discussed in this research. The data used in this research is primary and secondary data where the data primary in the form of statutory regulations. With this evidence, it is hoped that the court in its evidentiary process will be able to provide legal certainty to those seeking justice.